Persuasive Da'wah Approach from the Perspective of the Qur'an - Nurbini; Rifanda Putri, Nia (Munazzama: Journal of Islamic Management and Pilgrimage, 2025)
Persuasive da’wah is an approach that emphasizes gentleness, wisdom, and exemplary conduct in conveying Islamic teachings. This paper aims to explore the concept, foundation, and implementation of persuasive da’wah from the perspective of the Qur’an. This study employs a library research method with a qualitative-descriptive approach, which involves tracing, collecting, and analyzing primary sources in the form of verses from the Al-Qur’an and scholarly interpretations (tafsir), as well as secondary sources in the form of literature on the science of da'wah and Islamic communication. This paper examines Qur’anic verses that serve as the basis for persuasive da’wah, including Surah An-Nahl (16:125), Ali Imran (3:159), and Thaha (20:43–44). The findings reveal that the Qur’an emphasizes that da’wah should be carried out with hikmah (wisdom), mau‘izhah hasanah (good advice), and mujādalah billatī hiya ahsan (dialogue in the best manner). These principles affirm that da’wah is not merely the transmission of religious messages but a process of touching hearts and fostering spiritual awareness without coercion. In the context of modern society, persuasive da’wah is increasingly relevant as it promotes humanistic, dialogical, and contextual communication. Through this approach, da’wah serves not only as a means of spreading Islamic teachings but also as a medium for nurturing moral, social, and humanitarian values in accordance with the spirit of Islam as rahmatan lil ‘alamin (a mercy to all creation).